High-fidelity numerical modeling of a pneumatic PTO for floating oscillating water column devices (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In this work, a novel Smoothed Particle Hydrodynamics (SPH) implementation to model the pneumatic power take-off (PTO) system of floating oscillating water column (OWC) devices is presented. The working principle of an OWC relies on the compression and decompression of the air pocket formed by a water column oscillation in its chamber, which in turns generates an air flow that activates a turbine. Usually, for practical reasons, instead of simulating the full power train, an orifice plate is employed to replicate its effect [1], both numerically and experimentally. Previous work has analyzed the air–water interaction in the chamber of a floating OWC by means of mesh-based or mesh-less two-phase simulations [2,3].This research, instead, focuses on the influence of the varying air pressure on water inside the chamber using a single-phase SPH technique [4], implemented by coupling a “chamber model” to the SPH scheme within the DualSPHysics software. Such approach estimates the air pressure depending on the air flux through the OWC orifice and on a damping coefficient depending on the orifice size. In terms of numerical modeling, the air pressure is directly added to the SPH momentum equation at the chamber free surface. In addition, a novel six DOF volume tracking algorithm, which works both in 2D and 3D, is implemented to identify the water volume inside the floating OWC chamber at every integration time step. It relies on detecting a fictitious chamber inside the SPH one by defining some reference points and updating their position according to the roto-translations of the floating body.  By knowing the volume occupied by the fluid particles in the chamber, the air pressure inside the device is obtained and applied to the water free surface to mimic the behavior of the OWC. Simulations of a catenary moored dual-pontoon OWC device and a tension leg-moored one, are performed respectively in 2D and 3D to validate the methodology against experimental results and prove the accuracy of this implementation.Such a methodology is potentially applicable to various marine devices, since, in principle, the model chamber reference points can be defined for any arbitrary geometry. Moreover, to the authors’ knowledge, this work represents the first attempt at simulating free floating OWCs in a single-phase framework exploiting the coupling with an analytical model, hence improving the computational efficiency with respect to the analogous SPH two-phase simulations.[1] M. Morris-Thomas, et al. (2017). “An investigation into the hydrodynamic efficiency of an oscillating water column,” Journal of Offshore Mechanics and Arctic Engineering-transactions of The Asme - J OFFSHORE MECH ARCTIC ENG, vol. 129, 11.[2] Y. Zhang, et al., (2025). “A multi-phase SPH model for simulating the floatingowc-breakwater integrated systems,” Coastal Engineering, vol. 197, p.104658.[3] A. Elhanafi, et al. (2017). “Experimental and numerical investigations on the hydrodynamic performance of a floating–moored oscillating water column wave energy converter,” Applied Energy, vol. 205, pp. 369–390.[4] G. Zhu, et al. (2020). “Hydrodynamics of onshore oscillating water column devices: A numerical study using smoothed particle hydrodynamics,” Ocean Engineering, vol. 218, p.108226.